THE SOCIAL-PHILOSOPHICAL ANALYSIS OF THE POVERTY - Nargis Abdukhalilovna Alimatova (Journals Park Publishing, 2023)
In this article, the phenomenon of poverty is analyzed from a socio-philosophical point of view. It reveals the issues of classification of poverty, its difference from deep poverty, modern approaches to the criteria of poverty, the level of poverty in Uzbekistan. At the end of the article, attention is drawn to the role of the mahalla in poverty reduction in Uzbekistan.
Keywords: poverty, deprivation, consumer basket, socio-economic phenomenon.